Money and finance in Africa : the experience of Ghana, Morocco, Nigeria, the Rhodesias and Nyasaland, the Sudan, and Tunisia from the establishment of their central banks until 1962 - Jucker-Fleetwood, Erin Elver (London : George Allen & Unwin Ltd., 1964)
This book is a study that examines the major problems associated with the monetary and financial problems of emerging countries in Africa.
Includes index.
Includes bibliographical references: p. 322-330.
ne 21/01/2019
Loans
Keywords: Monetary policy; Finance; Banks and banking, Central; Credit